Application of Point-line Meshing Gear in Automobile Gearbox - Tan Fuchun; Wang Jun; Huang Hai; Wang Wei; Zou Jie; Li Haixiang (Jixie chuandong, 2017)
When point-line meshing gear is used in an automobile gearbox,it has the effect of reducing transmission series,increasing transmission ratio,enhancing strength,reducing noise,reducing volume and weight reduction etc. The parameter choosing transmission ratio distribution,calculating example and improved tooth number distribution of point-line meshing gears in an automobile gearbox are described. Several gearboxes are produced,and the noise is lower than involute gearbox,after using more than twenty months,the gearboxes run well and without tooth breaking and pitting.